Asuhan Keperawatan Klien yang Mengalami Defisit Nutrisi dengan Diabetes Melitus di RSAU dr. Esnawan Antariksa - Anwar Hidayat; Evi Vestabilivy (Jurnal Persada Husada Indonesia, 2021)
Diabetes Mellitus is a hyperglycemia disease characterized by absolute absence of insulin or a relative decrease in insensitivity of cells to insulin. Nutritional deficits are insufficient nutrient intake to meet metabolic needs. On both clients for 3 days. The purpose of this study is to obtain a description of the implementation of nursing care on clients who experienced Nutritional Deficit with Diabetes Mellitus in RSAU dr. Esnawan Antariksa. The research method used qualitative descriptive research method with intervention. Participants in this case study were two clients, two client family members, and two room nurses. Results and Discussion in this study that at the assessment stage on both clients found the subjective data both complain of no appetite, both clients both said weight loss, objective data both clients seem not appetite, both clients only spend ½ portion food. The priority of nursing diagnoses in both clients is nutritional deficits associated with insulin inadequacy. At the planning stage tailored to the established nursing diagnoses include goal setting and outcome criteria as well as independent and collaborative nursing interventions. Implementation of nursing is adjusted to the planning that has been prepared, where the main intervention is to advocate high-fiber foods so that the nutritional deficits experienced by both clients can be resolved. The evaluation of the nutritional deficit nutritional problems associated with inadequate insulin inadequacy is characterized by both clients saying appetite is good, seen in both clients consuming 1 serving, no signs of malnutrition, weight increases so nursing intervention is stopped. The authors conclude that the nursing action of providing high-fiber foods is one of the main nursing actions that are effective in overcoming the problem of nursing nutritional deficits in clients with Diabetes mellitus.